Definitive chemoradiotherapy versus neoadjuvant chemoradiotherapy followed by surgery in patients with locally advanced esophageal squamous cell carcinoma who achieved clinical complete response when induction chemoradiation finished: A phase II random. (September 2022) - Qian, Dong; Chen, Xi; Shang, Xiaobin; Wang, Yuwen; Tang, Peng; Han, Dong; Jiang, Hongjing; Chen, Chuangui; Zhao, Gang; Zhou, Dejun; Cao, Fuliang; Er, Puchun; et al.
Highlights: More than 40% of patients with esophageal squamous cell carcinoma (ESCC) exhibit pathological complete responses after neoadjuvant chemoradiotherapy (nCRT), and theoretically, active surveillance could be feasible in these patients. Compared with nCRT followed by surgery, definitive chemoradiotherapy was associated with equal survival for patients with ESCC who achieved clinical complete responses to induction chemoradiotherapy according to our criteria. Clinical response evaluation in our study predicted postoperative pathological response with a higher accuracy which results in an overall accuracy of 86.1%. Abstract: Background and purpose: More than 40% of patients with esophageal squamous cell carcinoma (ESCC) exhibit pathological complete responses (pCR) after neoadjuvant chemoradiotherapy (nCRT), and theoretically, these patients may be cured by CRT and omit surgery. This prospectively randomized pilot study compared definitive chemoradiotherapy (dCRT) with nCRT in patients with locally advanced ESCC who achieved clinical complete responses (cCRs) to nCRT. Materials and methods: Single center, randomized, open phase 2 study of 256 patients with locally advanced ESCC enrolled between April 2016 and November 2018. Immediately when nCRT finished, patients enrolled underwent response evaluations within 1 week. Patients with cCR were randomly allocated to undergo surgery (arm A) or complete CRT up to the definitive radiation dose (arm B). The primary end point was 3-year disease-free survival (DFS). Results: Finally, 71 patients were randomly assigned to the nCRT (n = 36) and dCRT (n = 35) arms. The median observation time was 35.7 months. The 3-year DFS rate was 56.43 % in arm A versus 54.73 % in arm B (hazard ratio [HR] = 0.862, 95 % confidence interval [CI] = 0.452 to 1.645, P = 0.652). The 3-year overall survival (OS) rates in arms A and B were 69.5 % and 62.3 % (HR = 0.824, 95 % CI = 403–1.688, P = 0.597), respectively. Conclusions: According to our treatment response evaluation criteria, survival of the patients with cCR after nCRT was not significant different between nCRT group and dCRT group. An optimized response evaluation strategy soon after nCRT may guide next therapy decisions for patients with locally advanced ESCC.